Char burnout characteristics of five coals below and above ash flow temperature: TG, SEM, and EDS analysis. (25th June 2016) - Zeng, Xiongwei; Zheng, Shu; Zhou, Huaichun; Fang, Qingyan; Lou, Chun
Highlights: Mass loss of chars burned above the FT is over 7.36% less than that below the FT. The unburned carbon particles are observed in the ashes that burned above the FT. The fused ash decreases the burnout ratio of char as the temperature exceeds FT. Abstract: At present, most research on coal combustion by thermo-gravimetric analyzer (TGA) are conducted under a variety of temperature-increasing rates from room temperature to high temperatures. One of the main limitations to the TGA procedure is that burning and burnout temperatures (generally below or around 1000 °C) are always lower than ash flow temperatures (FTs), (generally higher than 1100 °C). In this study, char samples from five types of Chinese coal were prepared and burned in a TGA at fixed temperatures below and above their respective FTs. All char and ash samples were then analyzed via SEM–EDS. With the same initial weight of 20 mg, the total mass loss in Mode I (combustion temperature higher than the FT) was 0.7–2.3 mg less than that in Mode II (combustion temperature lower than the FT), or about 7.36–23.29% of the initial mass. The SEM–EDS images also showed that the fused ash formed a shell around the char particle which decreased the char burnout ratio significantly when combustion temperature exceeded the FT. By contrast, when combustion temperature was below the FT, the ash samples presented separated, soft, and powder aggregation morphological characteristics without melting.